Towards Targeting the Aryl Hydrocarbon Receptor in Cystic Fibrosis - Matteo Puccetti; Giuseppe Paolicelli; Vasileios Oikonomou; Antonella De Luca; Giorgia Renga; Monica Borghi; Marilena Pariano; Claudia Stincardini; Lucia Scaringi; Stefano Giovagnoli; Maurizio Ricci; Luigina Romani; et al. (Hindawi Limited, 2018)
Tryptophan (trp) metabolism is an important regulatory component of gut mucosal homeostasis and the microbiome. Metabolic pathways targeting the trp can lead to a myriad of metabolites, of both host and microbial origins, some of which act as endogenous low-affinity ligands for the aryl hydrocarbon receptor (AhR), a cytosolic, ligand-operated transcription factor that is involved in many biological processes, including development, cellular differentiation and proliferation, xenobiotic metabolism, and the immune response. Low-level activation of AhR by endogenous ligands is beneficial in the maintenance of immune health and intestinal homeostasis. We have defined a functional node whereby certain bacteria species contribute to host/microbial symbiosis and mucosal homeostasis. A microbial trp metabolic pathway leading to the production of indole-3-aldehyde (3-IAld) by lactobacilli provided epithelial protection while inducing antifungal resistance via the AhR/IL-22 axis. In this review, we highlight the role of AhR in inflammatory lung diseases and discuss the possible therapeutic use of AhR ligands in cystic fibrosis.